2022
DOI: 10.21203/rs.3.rs-1412694/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Prevalence of Thyroid Dysfunction and Autoimmune Thyroid Disease in Patients with Rheumatoid Arthritis

Abstract: Background: Rheumatoid arthritis (RA) is one of the most common chronic non-organ-specific autoimmune diseases; meanwhile, autoimmune thyroid disease (AITD) is the most common organ-specific autoimmune disease that can lead to hypo or hyperthyroidism. Although the etiology of both diseases is complex with a combination of genetic and environmental factors, there are overlaps in genes contributing to the pathogenesis of both diseases. Numerous studies found a correlation between thyroid abnormality and RA in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…However, a consensus on this matter is not achieved (13). Several studies have established a higher prevalence of thyroid dysfunction, particularly overt hypothyroidism, anti-TPO positivity, and AITD among RA patients (14, 15). In addition, recent studies have also suggested that AITD comorbidity can exacerbate RA severity and activity (16).…”
Section: Discussionmentioning
confidence: 99%
“…However, a consensus on this matter is not achieved (13). Several studies have established a higher prevalence of thyroid dysfunction, particularly overt hypothyroidism, anti-TPO positivity, and AITD among RA patients (14, 15). In addition, recent studies have also suggested that AITD comorbidity can exacerbate RA severity and activity (16).…”
Section: Discussionmentioning
confidence: 99%